2020
DOI: 10.1016/j.neuron.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Circadian VIPergic Neurons of the Suprachiasmatic Nuclei Sculpt the Sleep-Wake Cycle

Abstract: Highlights d Specific VIP+ neurons of the SCN fire at night when most others are silent d Activating or silencing these VIP+ neurons controls nighttime but not daytime sleep d Circadian clockwork within these specific neurons times the daily ''siesta'' d The activity of these neurons, in turn, programs subsequent end-of-day alertness

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 79 publications
4
46
0
Order By: Relevance
“…We show how the Drosophila circadian system creates a dynamic internal reference of what environmental conditions should be. Many of the motifs we observed are conserved: Mammalian circadian clock neuron subpopulations are also active at different times (80)(81)(82)(83) and are linked by recurrent inhibition (84)(85)(86)(87)(88), suggesting that mammalian temporal estimation may operate using similar principles. The paradigm that we developed offers opportunities to understand the interface between internal models and sensory evidence.…”
Section: Discussionmentioning
confidence: 83%
“…We show how the Drosophila circadian system creates a dynamic internal reference of what environmental conditions should be. Many of the motifs we observed are conserved: Mammalian circadian clock neuron subpopulations are also active at different times (80)(81)(82)(83) and are linked by recurrent inhibition (84)(85)(86)(87)(88), suggesting that mammalian temporal estimation may operate using similar principles. The paradigm that we developed offers opportunities to understand the interface between internal models and sensory evidence.…”
Section: Discussionmentioning
confidence: 83%
“…Action potentials are a key output of neural circuits and SCN neuronal firing is used to communicate circadian timekeeping information to the rest of the brain 38 40 . To assess how baseline firing was altered by the absence of VPAC 2 receptor signaling, we used a microelectrode array (MEA) platform to record and compare spontaneous multi-unit spiking activity in the dSCN and vSCN of brain slices from WT and Vipr2 −/− mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We found that inhibition of SCN VIP neurons during the daytime did not delay locomotor activity offset (Fig. S3C), indicating that simple activation or inhibition of SCN VIP neurons during daytime cannot directly affect locomotor plasticity (Collins et al, 2020). Alternatively, SCN VIP neurons may not involve in mediating TRF-related behaviors.…”
Section: Resultsmentioning
confidence: 92%